Analyzes methods of ABNT NBR 15527/2007 for sizing rainwater water reservoirs in municipalities in the semiarid pernambucano in Brazil (Research, Society and Development, 2020)
The Brazilian semiarid region presents great challenges for the supply and management of water resources. Alternatively, rainwater harvesting systems (RWHS) are widely used. However, there are uncertainties about the methods of dimensioning the reservoirs of RWHS. ABNT NBR 15527/2007 standardizes six methods of reservoir dimensioning, in which their applications are related to the climatic specificities of the regions. Therefore, this work proposes the study of the applicability of standardized methods for the municipalities of Caruaru, Bezerros and Gravatá in the semiarid region of the state of Pernambuco. The objective is to evaluate the most appropriate method for each municipality, evaluating the guarantee of supply and the financial viability of execution. For this purpose, a hypothetical residence with a covered area of 160 m2 was established. The pluviometric regime was determined according to a historical series of 4 years for each municipality. Economic viability was verified based on the costs for execution of the reservoirs and financial savings based on local tariffs. As a result, it was seen that the Simulation and Australian Practical methods are the most proper, as they offer a higher rate of certainty in meeting demand, as well as because they also have a relatively quick estimated return on investment, compared to other methods.